Strengthening social media utilization among primary health center - Santi, Bryany Titi; Hadiyanto; Refi, Yasinta; Ekaputra, Anthony; Fitriah, Nur (Universitas Gadjah Mada, 2024)
Purpose: The COVID-19 pandemic changed health services in primary care settings. Puskesmas continued to provide information, education, and health promotions by utilizing social media, but how do they do it, and what do they need? Data still needs to be provided. This study will provide an overview of social media utilization and its organizational factors within Puskesmas in Jakarta. Method: This qualitative descriptive study was obtained through focus group discussions (FGD) and secondary data. Puskesmas was selected by sampling and analyzing social media (Instagram, Facebook, Youtube, and Twitter) at 42 centers and selecting four centers with the highest and 2 with the lowest utilization. Results: Instagram is a frequently used social media (95.2%). For organizational factors, in terms of planning, the social media officer has a monthly-annual plan for uploading materials. For organizations, there are divisions of tasks. The Head of the Health Center provides guidelines for direction, and the Head of Puskesmas directs the content. For control, the Head of the Health Center and Puskesmas evaluate the report monthly. Conclusion: Instagram is the most widely used, and the organizational factors are the availability of infrastructure, budget, team officers, and evaluation from the Head of the Health Center and Puskesmas. Only four Puskesmas were involved in this study, and selecting criteria based on four types of social media are limitations in this study to represent all Puskesmas that may be active in other social media such as WhatsApp and TikTok.